2011
DOI: 10.4314/ijbcs.v4i4.63053
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipid profile of Wistar albino rats fed palm oil-supplemented diets

Abstract: The effect of palm oil-supplemented diet on plasma lipid profile of Wistar albino rats was investigated by feeding the experimental animals with 20% palm oil-supplemented diets for 12 weeks. The plasma levels of Total cholesterol (TC), Triglycerides (TG), Low-density lipoprotein (LDL), and High-density lipoprotein (HDL) were determined at 4-, 8-, and 12-week intervals. The results showed significant (p<0.05) increases in TC (from 2.44+0.44 to 3.41+0.41), TG (from 1.72+0.51 to 2.46+0.19), and LDL (from 0.87+0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…The global burden of hypertension is enormous (Kearney et al, 2004), and has been recognized as the most common cardiovascular disorder and a leading cause of morbidity and mortality in both developed and developing countries (Goyal and Sarwate, 2014). Elevated plasma level of low density lipoprotein (LDL) fraction that contributes to hyperlipidaemia has been implicated in the development of atherosclerosis and progression of cardiovascular diseases (Onyeali et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The global burden of hypertension is enormous (Kearney et al, 2004), and has been recognized as the most common cardiovascular disorder and a leading cause of morbidity and mortality in both developed and developing countries (Goyal and Sarwate, 2014). Elevated plasma level of low density lipoprotein (LDL) fraction that contributes to hyperlipidaemia has been implicated in the development of atherosclerosis and progression of cardiovascular diseases (Onyeali et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Tholstrup et al (2011) reported that palm oil significantly increased LDL cholesterol (p <0.001) with 32 subjects compared with olive oil (Tholstrup, Hjerpsted & Raff, 2011). However, this oil is common in African and Asian food habits, mainly in rural areas where it is used in raw form (Ong & Goh, 2002;Oluba & Oyeneke, 2009;Onyeali, Onwuchekwa, Monago & Monanu, 2010;Oyewole & Amosu, 2010). We conducted a study with 2240 healthy subjects aged 18 years and more to verify the effect of palm oil consumption on anthropometric parameters (weight and height).…”
Section: Introductionmentioning
confidence: 99%
“…Dört hafta sonra palm yağı ile beslenen deney hayvanlarının trigliserid, serum LDL ve total kolesterol düzeylerinin artmasına rağmen, 12 hafta sonra kontrol grubuna kıyasla total kolesterol ve LDL düzeyleri önemli düzeyde düşmüştür. Araştırmacılar bu etkinin palm yağının A ve E vitamini içeriğinin yüksek olması ve antioksidan özelliği ile ilgili olabileceğini öne sürmüşlerdir (20). Özellikle tokotrienollerin hidroksimetilglutaril-KoA redüktaz enzim aktivitesini inhibe ettiği ve böylelikle kolesterol sentezini inhibe ederek serum kolesterol düzeylerini düzenlediği bildirilmektedir (15).…”
Section: Palm Yağının Sağlık üZerine Etkileri Palm Yağı Ve Kardiyovasunclassified